2012
DOI: 10.1016/j.proeng.2012.07.345
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of Electromagnetic Based Valveless Pump

Abstract: This study is a CFD analysis of electromagnetic based valveless pump in biomedical devices and biological MEMS (bioMEMS) application. The focus of the studies are designing a well performed pump where the required displacement of diaphragm can still be achieved even when the force applied is reduced and also a mechanism that requires low input current. Various parameters such as radius of the microcoil and diaphragm; and thickness of the magnet are compared to help choosing a proper pump. By using DesignModele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
(36 reference statements)
0
1
0
1
Order By: Relevance
“…Impedance pump is still on subjective deliberation and starting to gain interest due to its potential. Due to its intricate nature and reliance on some parameters, many researchers have simplified its model from various numerical studies [7][8][9][10] and identified the parameters and documented the behavior of the flow from experimental studies [11][12][13].…”
Section: Impedance Pumpmentioning
confidence: 99%
“…Impedance pump is still on subjective deliberation and starting to gain interest due to its potential. Due to its intricate nature and reliance on some parameters, many researchers have simplified its model from various numerical studies [7][8][9][10] and identified the parameters and documented the behavior of the flow from experimental studies [11][12][13].…”
Section: Impedance Pumpmentioning
confidence: 99%
“…O atuador eletromagnético leva vantagem nesse cenário por possuir um tempo de resposta rápido e ao mesmo tempo por oferecer um grande deslocamento da membrana de atuação, valores acima de 100µm. No entanto, a corrente máxima que passa pela bobina, quando esta está integrada ao dispositivo, deve ser cuidadosamente levada em consideração, pois pode causar o aquecimento excessivo do fluido e do dispositivo [110]. Além dessas vantagens qualitativas em relação a outros métodos de atuação, o eletromagnético foi escolhido para as aplicações desta tese por que possuía compatibilidade com os processos e facilidade de fabricação nos laboratórios disponíveis.…”
Section: Comparação Entre Os Métodosunclassified